Chronic Kidney Disease and Urological Disorders: An Overview - Lai, S.; Sciarra, A.; Pierella, F.; Pastore, S.; Piloni, L.; Salciccia, S.; Perrotta, A.M.; Protopapa, P.; Pintus, G.; Ricciuti, G.; Ciccariello, M.; Heland, M. V. (Current Signal Transduction Therapy, 2020)
Introduction: Chronic Kidney Disease (CKD) is a highly prevalent condition and it is a major risk factor for End-Stage Renal Disease (ESRD), cardiovascular disease, and premature death. Some congenital and acquired anomalies of the kidneys and lower urinary tract (CAKUT and CALUT) are well-known causes of CKD and ESRD, but often remain undiagnosed and their prevalence is underestimated. This study aims to provide an overview that considered mainly some of the major congenital and acquired urological diseases that could lead to renal clinical manifestations common even to the most widespread renal pathologies, for which often underdiagnosed. Materials and Methods: PubMed search was conducted for available English literature describing the actual knowledge on congenital and acquired urological disorders determining acute and chronic kidney disease. Prospective and retrospective studies as well as meta-analyses and latest systematic reviews were included. Results: Most of the studies examined and reviewed were discarded for wrong population or intervention or deemed unfit, and only 87 met the inclusion criteria for the review. The studies included in the review related to urological disorders that may determine chronic and acute kidney disease. Conclusion: Some urological diseases, as CAKUT and CALUT, especially in adults, show symptoms, as renal failure, proteinuria and hypertension, very common to other kidney diseases, for this reason may remain undiagnosed and their prevalence is not completely known. Therefore, in doubtful cases, non-invasive and inexpensive tests, as cystourethrogram, should be made, to rule out urological disorders and if necessary, ultrasonography, urography and scintigraphy, might allow a correct and early diagnosis of these defects and thus adequate therapy, preventing or at least slowing down an evolution toward CKD and ESRD.
Keywords: congenital anomalies of the kidney